Supply Chain Strategies and Methodologies—A Bibliometric Review - García-Alcaraz, Jorge Luis (Springer, 2023)
Supply chain strategies (SCS) have been gaining increasing interest given the recent disruptive events associated with wars and pandemics, where traditional SCS have proven insufficient. This article presents a bibliometric review of SCSs, analyzing the main trends, authors, institutions, and countries in which they are found, which will allow new SCS scholars to establish direct contact with the literature. PRISMA methodology is used to identify 1430 documents published from 1993 to 2021, and then VOSviewer and Bibliometrix software are used to analyze the information. Findings indicate that the trend of SCS publications is increasing, that its main area of application is Business, Management and Accounting, and that the main authors are Christopher M., Saputra J. and Wang S., who are also the ones who initiated this term two decades ago. Additionally, the publications on the topic are articles, conference papers, and book chapters, indicating that they have undergone a review process. It is concluded that SCS will continue to grow in initiator countries such as the United States of America and the United Kingdom. However, countries such as China and India will start to increase their academic output significantly.